External Ventricular Drain and Hemorrhage in Aneurysmal Subarachnoid Hemorrhage Patients on Dual Antiplatelet Therapy: A Retrospective Cohort Study. Issue 2 (11th April 2018) - Hudson, Joseph S; Prout, Benjamin S; Nagahama, Yasunori; Nakagawa, Daichi; Guerrero, Waldo R; Zanaty, Mario; Chalouhi, Nohra; Jabbour, Pascal; Dandapat, Sudeepta; Allan, Lauren; Ortega-Gutierrez, Santiago; Samaniego, Edgar A; et al.
Abstract: BACKGROUND: Stenting and flow diversion for aneurysmal sub arachnoid hemorrhage (aSAH) require the use of dual antiplatelet therapy (DAPT). OBJECTIVE: To investigate whether DAPT is associated with hemorrhagic complication following placement of external ventricular drains (EVD) in patients with aSAH. METHODS: Rates of radiographically identified hemorrhage associated with EVD placement were compared between patients who received DAPT for stenting or flow diversion, and patients who underwent microsurgical clipping or coiling and did not receive DAPT by way of a backward stepwise multivariate analysis. RESULTS: Four hundred forty-three patients were admitted for aSAH management. Two hundred ninety-eight patients required placement of an EVD. One hundred twenty patients (40%) were treated with stent-assisted coiling or flow diversion and required DAPT, while 178 patients (60%) were treated with coiling without stents or microsurgical clipping and did not receive DAPT. Forty-two (14%) cases of new hemorrhage along the EVD catheter were identified radiographically. Thirty-two of these hemorrhages occurred in patients on DAPT, while 10 occurred in patients without DAPT. After multivariate analysis, DAPT was significantly associated with radiographic hemorrhage [odds ratio: 4.92, 95% confidence interval: 2.45-9.91, P = .0001]. We did not observe an increased proportion of symptomatic hemorrhage in patients receiving DAPT (10 of 32 [31%]) vs those without (5 of 10 [50%]; P = .4508). CONCLUSION: Patients with aSAH who receive stent-assisted coiling or flow diversion are at higher risk for radiographic hemorrhage associated with EVD placement. The timing between EVD placement and DAPT initiation does not appear to be of clinical significance. Stenting and flow diversion remain viable options for aSAH patients.